A Rare Case of a Primary Cutaneous Desmoplastic Atypical Granular Cell Tumor. (April 2017) - Nakamura, Yasuhiro; Fujino, Takashi; Nagata, Koji; Imamura, Taichi; Teramoto, Yukiko; Asami, Yuri; Arai, Eiichi; Yamamoto, Akifumi
Abstract : Abstract: Granular cell tumors are uncommon neoplasms and a small number of these neoplasms have been reported as showing malignant behavior. Here, we report a rare case of a solitary granular cell tumor that exhibited atypical histology, including an extensive desmoplastic stroma, in a 69-year-old woman. The surgical specimen revealed localized areas of spindling cells, areas of cellular pleomorphism, and p53 overexpression. Based on previously published criteria, we classified this lesion as an atypical granular cell tumor. To date, only very few case reports have documented this desmoplastic variant of granular cell tumor. However, the classifications of benign, atypical, and malignant granular cell tumors are still controversial, owing to an overlap of morphological and immunohistochemical profiles and lack of consistent histological criteria. Additionally, it is unknown whether the histology of the desmoplastic variant in the present case is significant for the classification of granular cell tumors and prediction of patient prognosis. Regardless of these issues, awareness, and close follow-up are required because of potential recurrences of this rare variant of granular cell tumor.